Analysis and Design of a Web Based Fixed Asset Processing System in PT. Suka Maju - Sartika Lina Mulani Sitio; Nardiono (Jurnal Inotera, 2024)
financial reports issued by the finance department Problems that often occur at PT. Suka Maju is the whereabouts of fixed assets that are unknown, whether they are still in the warehouse or have been moved to another outlet/center. This is because sometimes the company opens a new branch or the head of the outlet needs fixed assets, then HR/GA moves the fixed assets from the warehouse to the outlet. Without communicating/reporting with central management so that central management does not know the position of the fixed assets. This results in central management not knowing the position of these assets and fixed asset reports not being in accordance with actual conditions. The main objective of this research is to design and develop a system that can manage company fixed assets effectively and efficiently by utilizing web technology. This system is expected to be able to increase accuracy and speed in the process of recording, tracking and managing fixed assets at PT Suka Maju. The research methodology used includes the needs analysis, system design, development and testing stages. At the needs analysis stage, interviews and observations were conducted to identify the needs and problems faced in managing fixed assets in the company. The results of this analysis become the basis for system design which includes database design, user interface, and system functionality. The research results show that this web-based fixed asset management system is able to increase the efficiency and effectiveness of asset management at PT Suka Maju. System users report improvements in the speed of access to information, accuracy of asset data, and ease of reporting and auditing assets. Thus, it is hoped that this system can be the right solution for PT Suka Maju in managing their fixed assets better